2010
DOI: 10.1002/jbm.b.31626
|View full text |Cite
|
Sign up to set email alerts
|

Thromboelastographic study of biomaterials

Abstract: Thromboelastography (TEG) is drawing more attention for clinical and in vitro studies of blood coagulation. It can be applied to evaluate the effects of both blood-soluble and insoluble biomaterials on whole blood coagulation from the beginning of coagulation through clot formation to the ending with fibrinolysis. TEG may also identify the relative contributions of various clotting factors, such as fibrinogen and platelets, to the overall coagulation process based on profiles of its variables using whole and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 122 publications
(312 reference statements)
0
36
0
Order By: Relevance
“…There have also been earlier studies which have shown that such assays based on PPP failed to demonstrate the effects of agents such as recombinant Factor VIIa. 13 In this study, we sought to avoid potential false negatives by using TEG which measures the entire coagulation pathway, including all redundancies, by exposing materials to whole blood and measuring subsequent clot formation. The TEG has been in existence for more than 50 years and its clinical use is well established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have also been earlier studies which have shown that such assays based on PPP failed to demonstrate the effects of agents such as recombinant Factor VIIa. 13 In this study, we sought to avoid potential false negatives by using TEG which measures the entire coagulation pathway, including all redundancies, by exposing materials to whole blood and measuring subsequent clot formation. The TEG has been in existence for more than 50 years and its clinical use is well established.…”
Section: Discussionmentioning
confidence: 99%
“…Although TEG was used briefly in biomaterials in the 1970s and 1980s, its use has fallen out of favor, partly due to difficulty in sample preparation. 15,16 Recently, Peng et al 13 reviewed the use of TEG for studying the effects of biomaterials on blood coagulation. A common methodology used by researchers in the case of blood soluble and blood substitute polymers is to mix these materials with the blood and then add the polymer diluted blood in the TEG cup to measure coagulation, but this method will not work for insoluble materials such as those of most interest for medical device design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEG is a test with time as horizontal ordinate to reflect blood clotting process and clot strength 8 . An anticoagulated whole blood sample (1 mL) and a sample to be tested (10 mg) were mixed well in a centrifuge tube and pipetted into a test cup.…”
Section: ) Thromboelastography Testmentioning
confidence: 99%
“…In contrast, its use as a research tool for evaluating the effectiveness of hemostatic agents, especially those insoluble in blood, is limited [13].…”
Section: Introductionmentioning
confidence: 99%